Transformative scenario planning : working together to change the future - Kahane, Adam (BK currents book., 2012)
The first book to describe a powerful new methodology for making progress on seemingly intractable societal challenges; Written by the originator of this methodology, this is a concise and concrete handbook for applying it in any applicable situation; Features vivid and often extraordinary examples from around the world of this methodology in action. People who are trying to solve tough economic, social, or environmental problems often find themselves frustratingly stuck. They cannot solve their problems in their current context; the larger system within which they are operating is too unstable or unfair or unsustainable. They cannot transform this system on their own or by working only with their friends or colleagues; the system is too complex to be grasped or shifted by any one person or organization or sector. And the actors whose cooperation would be necessary to transform the system don't understand or agree with or trust each other enough to work together. This book describes a powerful new methodology for dealing with this increasingly common set of challenges. Transformative Scenario Planning is a creative and constructive way for actors from across a whole system to work together to transform that system. It is a way for them to get unstuck and to move forward on solving their tough problems. Transformative Scenario Planning takes the well-established methodology of adaptive scenario planning--rigorously constructing a set of stories of alternative possible futures--and turns it on its head. It uses scenarios not only to understand and adapt to the future but also to challenge and change it. It offers a way for us to transform ourselves and our relationships with one another and thereby to transform the systems of which we are part.--